2020
DOI: 10.1016/j.jbankfin.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-border transmission of emergency liquidity

Abstract: Reproduction permitted only if source is stated. ISBN Non-technical summary Research QuestionIn response to the global financial crisis, the Federal Reserve Bank (Fed ) established several emergency facilities during the period from December 2007 to April 2010 peaking at USD 1.2 trillion at the end of 2008. The emergency facilities aimed at lifting liquidity constraints and mitigating bank lending contraction. Funds from the emergency facilities were accessible to U.S. banks as well as subsidiaries of foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The estimated cost advantage effects remain qualitatively stable, but they become smaller in magnitude. The estimated marginal effects of bank-specific covariates suggest that less profitable, less stable, and larger banks are more likely to operate foreign affiliates, which does not bode well considering affiliates' importance in propagating shocks (Cetorelli and Goldberg, 2012a;Kick et al, 2016). So far we have neglected the important insights from theoretical work by De Blas and Russ (2013) and Niepmann (2015Niepmann ( , 2016 that both competitive conditions in potential host markets as well as heterogeneous factor endowments across countries are crucial determinants of cross-border banking activities in general, and the entry choice of bank affiliates in particular.…”
Section: Foreign Affiliates: Cost Advantage or Other Factors?mentioning
confidence: 94%
See 1 more Smart Citation
“…The estimated cost advantage effects remain qualitatively stable, but they become smaller in magnitude. The estimated marginal effects of bank-specific covariates suggest that less profitable, less stable, and larger banks are more likely to operate foreign affiliates, which does not bode well considering affiliates' importance in propagating shocks (Cetorelli and Goldberg, 2012a;Kick et al, 2016). So far we have neglected the important insights from theoretical work by De Blas and Russ (2013) and Niepmann (2015Niepmann ( , 2016 that both competitive conditions in potential host markets as well as heterogeneous factor endowments across countries are crucial determinants of cross-border banking activities in general, and the entry choice of bank affiliates in particular.…”
Section: Foreign Affiliates: Cost Advantage or Other Factors?mentioning
confidence: 94%
“…Standard errors are clustered at the country level. We prefer this estimator to mitigate the zero-inflation bias in discrete regression settings (see King and Zeng, 2001;Baetschmann and Winkelmann, 2013;or Winkelmann and Staub, 2013). 13 To assess the relative importance of cost leadership in explaining foreign presence, we specify in Table 3 different (combinations of) fixed effects, bank-, and country-specific control variables.…”
Section: Foreign Affiliates: Cost Advantage or Other Factors?mentioning
confidence: 99%
“…This is especially true of banks that have low capital and liquidity. Kick et al (2018); Temesvary and Banai (2017) showed that banks with a lower capital to asset ratio, a high non-performing loan ratio and a lack of emergency liquidity tend to lower the lending growth. In addition, Popov and Udell (2012) documented that firms have been affected that attempted to get access to credit from banks that did not have steady capital, especially subsidiary banks.…”
Section: Hypotheses Formulationmentioning
confidence: 99%